Rancang Bangun dan Evaluasi Kinerja Troli Semi-Otomatis Bertenaga DC untuk Pengumpulan Brondolan Kelapa Sawit. - Rizki Faulianur; Zoel Fachri (J-Innovation, 2026)
Oil palm loose fruit collection is labor-intensive and can cause operator fatigue and low field efficiency. This study presents the design and performance evaluation of a 12 V DC-powered semi-automatic trolley for collecting loose fruits. The system combines a rotary sweeper, belt conveyor, and blower, all driven by DC motors and controlled using a simple ON/OFF circuit. Tests were conducted with loads of 2, 5, 7, and 10 kg. Evaluation covered collection and transport time, current consumption, power use, and operational stability. Operating time increased with load, reaching approximately 18, 26, 34, and 45 s, respectively. Although energy consumption rose at higher loads, the trolley remained stable and showed acceptable efficiency. Its integrated mechanism enables continuous collection, conveying, and cleaning while reducing manual effort and operator fatigue. The proposed trolley therefore offers a practical, ergonomic, and energy-efficient solution for improving productivity in oil palm plantations.